2009
DOI: 10.1159/000197862
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Body Composition in Adolescents Treated with Gonadotropin-Releasing Hormone Analogue Triptorelin Depot for Central Precocious Puberty: Data at Near Final Height

Abstract: Background/Aim: In children with central precocious puberty (CPP), gonadotropin-releasing hormone (GnRH) analogue treatment has been associated with an increase in body mass index (BMI). We evaluated BMI and body composition in adolescents treated with GnRH analogue at their near final height to assess the long-term effects of therapy on these parameters. Patients and Methods: We studied 20 patients (14.8 ± 1.6 years; 17 females) previously treated with triptorelin depot for CPP (3.75 mg/28 days) from 8.1 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 67 publications
0
20
0
7
Order By: Relevance
“…In accordance, prepubertal and pubertal insulin-sensitizing therapy has been associated with favorable effects on pubertal onset and progression and adiposity and adipocytokine profiles both during and after completion of puberty in girls at risk of early puberty (23,24,39). However, data on metabolic risk factors and body composition in girls previously treated with GnRHa are sparse and ambiguous (18,40). Thus, further studies are needed to accurately determine whether these metabolic alterations persist after discontinuation of GnRHa treatment and completion of pubertal maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, prepubertal and pubertal insulin-sensitizing therapy has been associated with favorable effects on pubertal onset and progression and adiposity and adipocytokine profiles both during and after completion of puberty in girls at risk of early puberty (23,24,39). However, data on metabolic risk factors and body composition in girls previously treated with GnRHa are sparse and ambiguous (18,40). Thus, further studies are needed to accurately determine whether these metabolic alterations persist after discontinuation of GnRHa treatment and completion of pubertal maturation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, inhibition of pubertal progression by GnRH agonist (GnRHa) treatment is associated with a continuous gain in adiposity despite suppression of gonadotropin and gonadal hormone secretion in such girls (16,18). Thus, GnRHa treatment does not seem to reverse the adverse body compositional changes associated with early maturation.…”
mentioning
confidence: 99%
“…In effect, while some authors report that GnRHa treatment is associated with weight gain [8,9,13,14,15,16,17], one study showed an increase only in those patients that were normal weight at study onset [18]. Other studies report no relationship between GnRHa treatment and an increase in body mass index (BMI) [4,10,11,12,19,20,21], while two studies demonstrated a decrease in BMI with GnRHa treatment [22,23]. These inconsistent findings could be related to several reasons including (1) different study designs, although most studies are retrospective; (2) heterogeneous etiology, including both organic and idiopathic CPP; (3) different age range and weight statuses at the onset of GnRHa treatment, and (4) distinct treatment strategies and follow-up times.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the speculation that HH per se plays a potential role in the physiopathology of obesity is tempting, but there is no evidence to support it. Moreover, the increased percentage of total fat mass reported by some authors reinforces the unfavorable effect of GnRHa on BMI and body composition in patients with idiopathic CPP [26][27][28].…”
Section: Discussionmentioning
confidence: 55%